The chemical reactivity of naphthols and their derivatives toward α-cyanocinnamonitriles and ethyl α-cyanocinnamates: A review of synthesis, reactions and applications of naphthopyrano - El-Wahab, Ashraf Hassan Fekry Abd; Mohamed, Hany Mostafa; El-Agrody, Ahmed Mohamed; Bedair, Ahmed Hammam (European Journal of Chemistry, 2013)
This review deals with synthesis and reactions of some naphthopyrano derivatives and their applications. The main purpose of this review is to present a survey of literatures on the reactivity of naphthols and their derivatives toward α-cyanocinnamonitrile or ethyl α-cyanocinnamate derivatives and the reactions of β-enaminonitriles and β-enaminoesters with different electrophiles followed by nucleophilic reagents. Some of these reactions have been applied successfully to the synthesis of biologically important compounds.